2022
DOI: 10.3389/fenrg.2021.709582
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Efficiency Evaluation and Spatiotemporal Characteristics Analysis of the Linkage Development of the Logistics Industry and Manufacturing Industry

Abstract: The logistics and manufacturing industries are basic industries that support social development. First, this study classifies the carbon emissions from the logistics industry and pollution emissions from the manufacturing industry as undesirable outputs and evaluates the ecological efficiency of the logistics and manufacturing industries in the Yangtze River Delta from 2006 to 2016 by using the unexpected slacks-based measure (SBM) model. Second, the study analyzes the spatial differences in industrial correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In that way, more effort and resources can be channelled towards improving the core business of the manufacturing establishments. Therefore, it is paramount to understand the linkages between the logistics and manufacturing industries (Zheng et al, 2022).…”
Section: Relationship Between Logistics and Different Sectors Of The ...mentioning
confidence: 99%
“…In that way, more effort and resources can be channelled towards improving the core business of the manufacturing establishments. Therefore, it is paramount to understand the linkages between the logistics and manufacturing industries (Zheng et al, 2022).…”
Section: Relationship Between Logistics and Different Sectors Of The ...mentioning
confidence: 99%
“…For example, Zhang and other scholars have demonstrated through the nuclear density curve that the level of China's industrial ecological efficiency shows a downward trend, and that polarization still exists but is weakening [21]. The spatial distribution characteristics of ecological efficiency are mainly analyzed from the perspectives of a region [22] and a city [23]. For example, Li pointed out that industrial ecological efficiency at the regional level of 30 provinces and cities in China had prominent agglomeration characteristics, and that the nearest neighbor effect is significant [24].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies have shown that supply chain entities involved in manufacturing and logistics can obtain more benefits by performing green contracts [10], and theoretically, the deepening of the integration of "two industries" will help to increase economic output and reduce carbon emissions [11]. Therefore, studying the ecological efficiency of the logistics industry and the manufacturing industry has important theoretical and practical significance for promoting the high-quality development of these industries, promoting the sustainable green growth of the regional economy, realizing the transformation and upgrading of industrialization, and realizing the development of China's low-carbon economy [12][13][14].…”
Section: Of 20mentioning
confidence: 99%